PENGARUH SEDIMENTASI BREAKWATER TERHADAP KOMUNITAS MAKROZOOBENTOS DI PESISIR SEMARANG - Ari Kristiningsih; Mardiyana Mardiyana (JURNAL PERIKANAN TROPIS, 2020)
Semarang is one of the main transportation crossing along the North coast of Java, which is very vulnerable to environmental damage. One of the damage is the beach abrasion that threaten in several point di Semarang coastal area. To overcome this problem then build  the construction of wave retaining buildings such as breakwater. Breakwater will reduce the rate of abrasion, because breakwater can break waves dan make its power reduced before it reaches the shoreline, so that the rate of abrasion can be compressed.Breakwater slowly will affect to the ecosystem by its sedimentation because of the  material accumulation and the become solidified. From this sediment will become a habitat to several organism. This research  was held from December 2016 - January 2017 at Semarang coastal area that divided into two station which is Station 1 at Mangkang area (West Semarang) and station 2 at Tambak Lorok area (North Semarang). The purpose of this research is to see the habitat of the organism that lived in sedimentation area around  the breakwater. The organism which is the object of research is macrozoobenthos. Macrozoobenthos is made an object of the research because of the nature of these organism whose lives are settled at the bottom of the coastal. The method used in this research is descriptive comparative. Based on research of the study makrozoobenthos has been found in each station from several classes . Polychaeta is a genus that dominates at every location because muddy sand is its main habitat.